2022
DOI: 10.55493/5002.v12i8.4587
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management and other Factors Preventing Fraudulent Financial Reporting by State-Owned Enterprises in Indonesia

Abstract: This study aims to provide an overview of the effects of risk management and the implementation of good corporate governance (GCG), and the effectiveness of the internal audit function on the prevention of fraudulent financial reporting and its impact on the quality of financial reporting of state-owned enterprises (SOEs) in Indonesia. Questionnaires are used to determine risk management and other factors that influence each other and their impact on the quality of financial reporting. The questionnaire and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Given that fraudulent acts are often hidden and rarely made public, firms need to manage their operational risks, which include the process of identification, assessment, analysis, monitoring and control of operational risks with good sound of corporate governance. Meanwhile, Novatiani et al (2022) highlighted that the establishment of risk management committee (RMC) provides oversight role of organization's risk management strategies, policies and processes which can serve as an important governance support mechanism. Their result found that risk management can prevent false financial reporting as good risk management creates innovation, embeds courage to take risks and inculcates attention to detail.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Given that fraudulent acts are often hidden and rarely made public, firms need to manage their operational risks, which include the process of identification, assessment, analysis, monitoring and control of operational risks with good sound of corporate governance. Meanwhile, Novatiani et al (2022) highlighted that the establishment of risk management committee (RMC) provides oversight role of organization's risk management strategies, policies and processes which can serve as an important governance support mechanism. Their result found that risk management can prevent false financial reporting as good risk management creates innovation, embeds courage to take risks and inculcates attention to detail.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…These results align with Almasarweh et al (2022), who found that RM positively affects performance. Furthermore, RM is also known to prevent fraudulent financial reporting (Novatiani et al, 2022) reduce inventory (Markou and Corsten, 2021) and improve the project's efficiency and performance (Kallow et al, 2022). Then, it also reduces cost (Upreti et al, 2022) improves the decision-making process, program stability and problem-solving (Oehmen et al, 2014) reduces financial losses and presents opportunities (Juul Andersen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(2022), who found that RM positively affects performance. Furthermore, RM is also known to prevent fraudulent financial reporting (Novatiani et al. , 2022) reduce inventory (Markou and Corsten, 2021) and improve the project's efficiency and performance (Kallow et al.…”
Section: Introductionmentioning
confidence: 99%
“…Davidson [15] analyzed 1805 executives and found that executives suspected of fraud had stronger equity incentives than executives in similar positions in nonfraudulent companies, and that equity incentives for all members of the top management team could be considered when identifying financial fraud. Novatiani et al [17] analyzed the data of 90 state-owned enterprises by SEM-PLS and found that the effectiveness of the internal audit function could prevent financial statement falsification. The study of financial fraud focuses on how to detect, identify, and prevent companies or individuals who intentionally fabricate false information in their financial reports to deceive investors.…”
Section: Introductionmentioning
confidence: 99%